ChemInform Abstract: Ru‐Catalyzed Direct C—H Amidation of 2‐Arylbenzo[d]thiazoles with Sulfonyl Azides. Issue 6 (February 2015) - Zhou, Xiaoli; Luo, Puying; Long, Ling; Ouyang, Meizhen; Sang, Xiaoyan; Ding, Qiuping
Abstract In contrast to aryl‐substituted benzothiazoles their hetaryl‐substituted analogues such as 2‐(furan‐2‐yl)benzo[d]thiazole and 2‐(pyridin‐4‐yl)benzo[d]thiazole fail to supply the corresponding products.